Analisis Sistem Pengendalian Internal Penggajian Karyawan Pada PT. Penjaminan Jamkrindo Syariah - Risma Febriyanti Putri RM; Hesti Agustin; Umrahwati Ilyas; Sri Wahyuni; Juandri Sangka (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to analyze the effectiveness of the internal control system of employee payroll at PT Penjaminan Jamkrindo Syariah. The research was conducted using a qualitative descriptive approach through literature study and analysis of payroll processes within the company. The payroll process in PT Jamkrindo Syariah consists of several stages, including employee data management, attendance recording using fingerprint, payroll calculation with specially designed Excel worksheets, verification and authorization, salary payment via bank transfer, accounting recording, and documentation. The results indicate that the company has implemented a fairly good payroll procedure supported by technology and proper documentation, which promotes efficiency, transparency, and accountability. The strengths of the system include the use of fingerprint for accurate attendance, semi-automated Excel calculation to minimize human errors, and complete payroll documentation. However, several weaknesses remain, such as the lack of segregation of duties, the absence of dual authorization in payroll approval, and the risk of manipulation when the fingerprint system fails. These weaknesses are inconsistent with internal control theories and may violate Islamic principles of justice (al-‘adl) and trustworthiness (amanah). Overall, the internal control system of payroll at PT Jamkrindo Syariah is adequate but needs improvements to enhance effectiveness and compliance with sharia values.).